(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Epilepsy is a common disorder of brain that is not well controlled via drugs available for it. Gephyrin, a well-known inhibitory synaptic regulator, has a role in epilepsy. Additionally, significant development of oxidative stresses tends to be involved in epileptic seizure pathophysiology that giving rise to neuronal cell death. Zizyphus spina christi is a vastly available Iraqi tree and its leaves have several beneficial effects on central nervous system level. Objective: To investigate the possible neuroprotective effect of crude Zizyphus spina christi extract in kindling model induced. Methods: The removed brains of forty albino male mice from four separate groups were exposed to immunohistochemical test for gephyrin, glutathione, and NeuN expressions. Results: The data found that pretreatment with Zizyphus spina christi crude extract shows highly significant difference (P value